Interoperability in e-Government Solutions: The Case of Brazilian Federal Universities - Oliveira, Alberto; Eler, Marcelo (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2017)
Governments use Information and Communication Technology (ICT) to provide citizens, organizations and governments with online services and tools. One of the key factors in this context is system interoperability, since it promotes the exchange of information among systems in different levels. Achieving high levels of interoperability, however, is challenging because it involves different concepts, business processes, standards, languages, ontologies and laws. The Brazilian government has defined the e-PING Interoperability Standards to specify the guidelines for achieving interoperability in different levels, but many public organizations cannot completely implement the interoperability aspects in their solutions. Therefore, the purpose of this paper is to present an investigation we conducted with the ICT departments of the Brazilian federal universities to understand whether and how they use the e-PING interoperability standards, and what are the main challenges. Results show that most universities do not fully implement interoperability requirements mainly because of a shortage of ICT staff, lack of knowledge and lack of clear instructions on how to achieve interoperability using the e-PING standards. Such findings allow us to identify several improvements on the Brazilian egovernment strategy.